The uses of technology in the educational process and its implications for science and the learner - Benarioua, Amel (Journal of Human Sciences, 2023)
This study aims at an objective and scientific examination of the reality of the use of various technology and modern technologies in the educational process, and to know the extent of the impact of the practice of technology in the educational and educational process, because the technical practice penetrated all stages of the educational process, and it constitutes a criterion for the superiority of educational systems over others. It is an international competitive feature, and through the results of the previous traditional educational systems, and contemporary educational systems, it will become clear to what extent technology affects education, and therefore the following question can be answered: What are the implications of using technology in the educational process ?